Improving decisions under uncertainty 1 - Payne, John W. (Henry Stewart Talks, 2011)
Making decisions about uncertain futures, The classic decision tree structure, Dealing with uncertain events, Influence diagram, "Known" uncertain events, Assess knowledge of the known unknowns, Two measures of belief